The birth of the archive : a history of knowledge - Friedrich, Markus (Cultures of knowledge in the early modern world., 2018)
The Birth of the Archive' traces the history of archives from their emergence in the Late Middle Ages through the Early Modern Period, and vividly shows how archives permeated and fundamentally changed European culture. Archives were compiled and maintained by peasants and kings, merchants and churchmen, and conceptions of archives were as diverse as those who used them. The complex, demanding job of the archivist was just as variable: archivists might serve as custodians, record-keepers, librarians, legal experts, historians, scholars, researchers, public officials, or some combination thereof; navigating archives was often far from straightforward. The shift of archival storage from haphazard collections of papers to the methodically organized institutionalized holdings of the nineteenth century was a gradual, nonlinear process.